(untitled) (London Journal of Research In Computer Science and Technology, 2026)
This article entails a quantitative analysis of the association between cyberbullying crude and number of user subscribers and uploads on YouTube. Of the several numbers of variables listed in the said dataset from Kaggle.com, the variables of comments, subscribers and uploads were found to be continuous. The data included 3464 YouTube user ids, and were analyzed using Descriptives, Normality Tests and Spearman’s Rho on SPSS. The findings included non-linear, positively skewed, non-normal distribution. The correlation analysis depicted a slight positive association between User subscribers and rude comments, whereas no connection between User uploads and crude comments. Future work to focus on other factors influencing hurtful commenting on YouTube.